Mechanisms of the Stimulation of Import Substitution in the Construction Industry - Kotlyarova, Svetlana Nikolayevna (Economy of Regions, 2016)
The issues of the dependence on imports and import substitution are the major factors in the development of the domestic economy. The subject matter of the research is the dependence of construction industry on imports in the area of foreign technology, it is aimed at identifying the scope of the problem and justifying the mechanisms to overcome it. The article substantiates the relevance and importance of import substitution in the production of construction materials and equipment. Import substitution in the construction industry can be implemented in two main ways, requiring different approaches in supporting and encouraging. Firstly, there is the substitution of products used in construction, aimed at minimizing the risk of disruption of the supply of imported products for construction purposes and the predominant use of domestic analogues of imported products for construction purposes. Secondly, there is the substitution in the technologies of production of goods used in construction, focused on stimulating the development of the domestic production of competitive products and technological and managerial modernization of the construction materials industry, construction industry. The process of import substitution in the construction industry have a number of limitations. In this connection, the article discusses the opportunities and constraints for import substitution. A special attention is paid to the practice of the formation of regional construction clusters as a tool of implementing the policy of import substitution. The purposes and principles of the development of clusters, sources of initiatives, used systems of transfer and knowledge and innovations are considered critically. The conclusion is made about the need for the strategic development of new products for the construction market and domestic research and development projects within the framework of cross-sectoral clusters. The basic forms of state support required for the implementation of the import substitution policy in the construction industry are substantiated. These are organizational, administrative and economic measures, whose implementation during the transition to the import substitution can lead to the reduction in the cost of construction materials. In the conclusion, the article states the priorities in the support of import substitution policies for the construction industry. The conclusions and recommendations proposed in the paper can be used by the federal and regional authorities in the development and adoption of strategic documents of the construction industry, in the planning of spatial development of the territories.